PENGEMBANGAN MEDIA PEMBELAJARAN DESAIN BUSANA DIGITAL BERBASIS ANDROID PADA MATA KULIAH APLIKASI KOMPUTER TERAPAN DI JURUSAN PKK FT UNM - Ayusnia Yusuf; Abdul Muis Mapalotteng; Syamsidah (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2021)
This research aims to discover (1) the stages of developing android-based digital fashion design learning media in Applied Computer Application Course; (2) the validity, effectiveness, and practicality of android-based digital fashion design learning media in Applied Computer Application Course. The research method used was Research and Development with ADDIE development model. The research subjects were 26 students and 2 lecturers of the PKK FT UNM. Data collection was obtained through documentation, observation, and questionnaire and analyzed by using quantitative descriptive statistical technique. The results of the research on the development of android-based digital fashion design learning media were conducted through the following stages: (1) Analysis; (2) Design; (3) Development; (4) Implementation, and (5) Evaluation. The quality of the learning media is stated as very valid by the media expert validator with a value of 94.12% which is in very valid category and the material expert with a value of 100% which is in very valid category. The practicality of the media based on the observation of students’ activities scored 88.75% in very active category, lecturer’s activities scored 93.75% in very active category, and the students’ response questionnaire scored 93.66% in very good category. The effectiveness is stated based on the results of the learning test, obtaining an average value of 91.15 with an A value index and students’ performance assessments obtaining an average of 90.40 with an A- value index where all students are stated to have passed. Therefore, the digital fashion design learning media is feasible to be used in the Applied Computer Application Course in the PKK FT UNM.